Perceptions of female teenagers in the Tshwane District on the use of contraceptives in South Africa - Ntswaleng S. Tabane; Mmapheko D. Peu (AOSIS, 2015)
Background: Perceptions of female teenagers in the Tshwane District contribute to the nonuseand or discontinued use of contraceptives as evidenced by increased levels of unplanned pregnancies. Objective: The objective of this study was to explore and describe the perceptions of female teenagers in the Tshwane District on the use of contraceptives. Methods: A qualitative, explorative, descriptive approach was followed in this study. The population comprised of pregnant female teenagers who were purposively selected. Data were collected using unstructured individual interviews on a face-to-face encounter in a natural setting. Data were analysed using the discourse method of data analysis. Results: The following perceptions on the use of contraceptives emerged: Perceptions on the use of contraceptives, emotions, contraceptive effects, social pressure and education on contraceptives. Teenagers' perceptions were predominantly negative with unfounded fears. Though the teenagers were aware of the importance of the use of contraceptives, motivation to pursue contraception was lacking. Teenagers verbalised to be uncommitted as well. Conclusion: Various perceptions of female teenagers in the Tshwane District on the use of contraceptives were explored and described. It was noted that all the teenagers interviewed had great remorse and feelings of guilt regarding their behaviour of not using contraceptives.Their need for re-education was cited and seen as motivational enough to encourage the use of contraceptives at primary health care settings. Therefore, the study recommended that health education programmes should be restructured to effectively influence the female teenagers'perceptions positively and to promote the use of contraceptives.